The fatigue fracture mechanism of Al7075 aluminum alloy clinching joints. (March 2023) - Zhang, Yue; Lu, Yan; Peng, Ruitao; Xu, Honghe; Zhu, Linwei; Wang, Tao
Lightweight aluminum alloys are widely used in automotive structural parts. Clinching (press-joining) is one of the most promising alternatives to welding for joining aluminum alloys, and as the failure of the joint is mainly caused by fatigue, the fatigue properties of the clinched joints directly affect the reliability and safety of the connected specimens. To gain a deeper understanding of this phenomenon, the static mechanical and fatigue properties of Al7075 aluminum alloy single-lap clinched joints were studied using static strength and tensile-tensile fatigue tests. The F–N curves of the joints were fitted using a straight-line and three-parameter power function method. The fractured samples and wear scars were analyzed by scanning electron microscopy and energy-dispersive spectroscopy. The results showed that the neck of the clinched joint and the upper sheet near the joint experienced the highest degree of fatigue fracture, the fretting wear debris consisted mainly of alumina and metallic aluminum, and the fretting wear was of a mode that differed from the two modes identified in the literature that we have dubbed "upper sheet inter-sheet region fretting wear."